Habitação Mínima e Apropriação do Espaço: O Bairro Rainha D. Leonor - Ana Patrícia da Silva Leal e Lima (2012)
The purpose of this work is to deepen the understanding of some forms of appropriation of space in minimum dwelling. The subject of this thesis focuses on Rainha D. Leonor's housing estate, located in Porto. Being composed by minimum dwellings this housing estate was recently object of rehabilitation, almost 60 years after its construction. The relations between the inhabitant and his house went through a long and diverse process of space appropriation, characteristic of this housing estate. Initially, and in order to clarify the development of minimum dwelling, since the early twentieth century, it was made an approach to themes that include/cover notions such as: minimum, human needs, the ideals of the international and national Modernist Movement. In addition, another subject of discussion, concerning the city of Porto, focuses on the dwelling's critical conditions. Here are discussed the measures and plans to solve the housing problems, connected to that period, covering the Plano de Melhoramentos para a cidade do Porto 1956-66. During the development of this specific study about Bairro Rainha D. Leonor two different moments are analyzed: before and after rehabilitation. The inhabitant's lifestyles, their daily practices and ways of living in this neighborhood are studied in both moments, perceiving their differences. The spatial changes in the houses between those two moments (before and after the rehabilitation) lead to different reactions by the inhabitants to their houses, showing their adjustments to the different spaces. This work allows to understand what is the meaning of living in minimum dwellings, and the mechanisms used to appropriate these houses.